2005
DOI: 10.1111/j.0022-1112.2005.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Pantophysin (Pan I) locus divergence between inshore v. offshore and northern v. southern populations of Atlantic cod in the north‐east Atlantic

Abstract: More than 6000 cod Gadus morhua, sampled in coastal and offshore waters stretching from the Barents Sea down to the North Sea, were analysed for frequencies of alleles at the scnDNA pantophysin locus (Pan I) [formerly called synaptophysin (Syp I)]. The significant allele frequency difference between the two major stocks of cod in Norway, north-east Arctic cod (NEAC) and Norwegian coastal cod (NCC), was upheld in all years of the investigation (1993 to 2001), and applied both to larval cod and post-juveniles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 46 publications
9
108
2
1
Order By: Relevance
“…Variation in PanI has been correlated with environmental factors, including water temperature, salinity, depth, latitudinal gradients and inshore/offshore migrations (Beacham et al 2002, Case et al 2005, Sarvas & Fevolden 2005, with potential fitness effects reported (Otterlei et al 1999, Case et al 2006, Jónsdóttir et al 2008. The patterns are not consistent across studies and geographic regions, however, indicating that the selective pressures may be complex (Jónsdóttir et al 2008).…”
Section: Natural Selection and Local Adaptationmentioning
confidence: 99%
“…Variation in PanI has been correlated with environmental factors, including water temperature, salinity, depth, latitudinal gradients and inshore/offshore migrations (Beacham et al 2002, Case et al 2005, Sarvas & Fevolden 2005, with potential fitness effects reported (Otterlei et al 1999, Case et al 2006, Jónsdóttir et al 2008. The patterns are not consistent across studies and geographic regions, however, indicating that the selective pressures may be complex (Jónsdóttir et al 2008).…”
Section: Natural Selection and Local Adaptationmentioning
confidence: 99%
“…This possibility cannot be dismissed, but the major reason for variable Pan I allele frequencies in catches of cod from these waters, both spatially and temporally, is probably attributable to varying proportions of NEAC and NCC in the catches. This holds true for both adult fish (Sarvas & Fevolden 2005a,b, Westgaard & Fevolden 2007) and 0-group juveniles (Fevolden et al 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Sarvas & Fevolden 2005a). The innermost known spawning site of that fjord, Bergneset, displayed sex ratios that were at least as skewed as in Malangen (9 of 10 fish on average over all study years were males) but the Pan I A frequencies were lower, down to 57% one year, as compared to the steady 90% in Malangen.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations